Comparative In vitro antibacterial activity of nemonoxacin and other fluoroquinolones in correlation with resistant mechanisms in contemporary methicillin-resistant Staphylococcus aureus blood isolates in Taiwan - Pao -Yu Chen; Mao-Wang Ho; Po-Liang Lu; Hung-Jen Tang; Cheng Len Sy; Jann-Tay Wang; Taiwan Staphylococcus aureus Consortium (TSAC) (Annals of Clinical Microbiology and Antimicrobials, 2025)
Abstract Background Nemonoxacin is a new quinolone with an antibacterial efficacy against methicillin-resistant Staphylococcus aureus (MRSA). Certain sequence types (STs) have been emerging in Taiwan, including fluoroquinolone-resistant ST8/USA300. It’s an urgent need to determine nemonoxacin susceptibility against ST8/USA300 and other emerging lineages, if any. Additionally, molecular characterization of nemonoxacin resistance among different lineages has yet to be defined. Methods Non-duplicated MRSA blood isolates from five hospitals during 2019–2020 were collected and genotyped by pulsed-field gel electrophoresis, and further correlated to their STs. Antimicrobial susceptibility testing for all antibiotics was performing by using Sensititre standard panel, except nemonoxacin by using agar dilution method. Selected isolates with nemonoxacin MICs ≥ 0.5 mg/mL were sequenced for quinolone resistance-determining regions (QRDRs). Results Overall, 915 MRSA isolates belonged to four major lineages, ST8 (34.2%), ST59 (23.5%), ST239 (13.9%), and clonal complex 45 (13.7%). Two-thirds of tested isolates were non-susceptible to moxifloxacin, especially ST8/USA300 and ST239. Of them, proportions of nemonoxacin non-susceptibility by a tentative clinical breakpoint (tCBP) of 1 µg/mL among four major lineages appeared to be different (P = 0.06) and highest in ST239 (22.2%), followed by ST8/USA300 (13.5%). Among 89 isolates sequenced, 44.1% of ST8 and all ST239 isolates had ≥ 3 amino acid substitutions (AAS) in gyrA/parC (group A) or 2 AAS in gyrA/parC with additional AAS in gyrB/parE (group B). Compared to other AAS patterns, isolates in group A had the greatest non-susceptible proportions to nemonoxacin (86.9%; overall/pair-wised comparisons, P < 0.05). Conclusions Our study confirmed ST8/USA300 MRSA has disseminated in Taiwan. Using a tCBP defined by a higher parenteral daily dosage, nemonoxacin retained potency against moxifloxacin non-susceptible isolates. Patterns of AAS in QRDRs among different lineages may contribute to difference of nemonoxacin susceptibility.